Differential effector gene expression underpins epistasis in a plant fungal disease. - Phan, Huyen; Rybak, K.; Furuki, Eiko; Breen, S.; Solomon, P.; Oliver, Richard; Tan, Kar-Chun (Wiley, 2016)
Fungal effector-host sensitivity gene interactions play a key role in determining the outcome of septoria nodorum blotch disease (SNB) caused by Parastagonospora nodorum on wheat. The pathosystem is complex and mediated by interaction of multiple fungal necrotrophic effector-host sensitivity gene systems. Three effector-sensitivity gene systems are well characterised in this pathosystem; SnToxA-Tsn1, SnTox1-Snn1 and SnTox3-Snn3. We tested a wheat mapping population that segregated for Snn1 and Snn3 with SN15, an aggressive P. nodorum isolate that produces SnToxA, SnTox1 and SnTox3, to study the inheritance of sensitivity to SnTox1 and SnTox3 and disease susceptibility. Interval quantitative trait locus (QTL) mapping showed that the SnTox1-Snn1 interaction was paramount in SNB development on both seedlings and adult plants. No effect of the SnTox3-Snn3 interaction was observed under SN15 infection. The SnTox3-Snn3 interaction was however, detected in a strain of SN15 in which SnTox1 had been deleted (tox1-6). Gene expression analysis indicates increased SnTox3 expression in tox1-6 compared to SN15. This indicates that the failure to detect the SnTox3-Snn3 interaction in SN15 is due - at last in part - to suppressed expression of SnTox3 mediated by SnTox1 Furthermore, infection of the mapping population with a strain deleted in SnToxA, SnTox1 and SnTox3 (toxa13) unmasked a significant SNB QTL on 2DS where the SnTox2 effector sensitivity gene, Snn2, is located.This QTL was not observed in SN15 and tox1–6 infections and thus suggesting that SnToxA and/or SnTox3 were epistatic. Additional QTLs responding to SNB and effectors sensitivity were detected on 2AS1 and 3AL.